Inflammaging, a Common Factor in the Development of Sarcopenia and Metabolic-Associated Liver Disease (MAFLD) - Gonzalo Jorquera; Francisco Javier Cubero (Livers, 2022)
Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease in Western countries, with its prevalence increasing annually [...]